Analisis Kuantitatif pada Formulir Resume Medis Rawat Inap di RSUD Praya Lombok Tengah - Lalu Muhammad Sadam Husen (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Medical records are files that contain notes and documents regarding patient identity, examinations, treatment, procedures and other services that have been provided to patients. Notes are writings made by a doctor or dentist regarding actions carried out on patients in the context of health services. Based on the results of a preliminary case study conducted at the Praya Regional General Hospital in June 2023, when carrying out the analysis there were incomplete medical record files due to staff negligence so there were still incomplete files. Of the 50 medical record files analyzed, there were 5 (10%) incomplete files in the patient identification review, 8 (16%) incomplete files in the Authentication review, 8 (16%) incomplete files in the review of important reports, 8 (16%) incomplete files in the review of important reports, reviewing important records, there were 9 (18%) files that had not been completed. This research aims to determine the effectiveness of the disease classification system using the international classification for medical records (ICD-10) at the Praya Regional General Hospital. This case study aims to describe the complete description of the accuracy of diagnosis codes for internal medicine cases at the Praya Regional General Hospital. So that a sample of 93 medical record files was produced. This sampling technique used a simple random sampling technique. From the results of observations of the identification review of 93 medical record documents for inpatients at Praya Regional Hospital, it shows that the medical resume form (RM.14.3) showed a percentage of completeness (80.64%) and (19.35%) incomplete patient names and record numbers. medical, in the date of birth item the percentage of completeness was obtained (73.11%) incomplete (26.88%), and gender the percentage of completeness was obtained (83.87%) incomplete (16.12%). 89.24%) incomplete and (10.75%) which is complete from the percentage (100%). The results of research related to calculating the completeness of filling out the Authentication review on medical resumes at Praya Regional Hospital, it was found that the percentage of completeness of the full name of the doctor in charge of the patient (DPJP) (76.5%) was incomplete (23.5%), in the signature item of the doctor in charge answer the percentage of completeness (76.5%) and incompleteness (23.25%) in the signature item of the patient or patient's family, the percentage of completeness (89%) and incompleteness (10.75%)